Hybrid Power Electronic Transformer Model for System-Level Benefits Quantification in Energy Distribution Systems - Prystupczuk , Federico; Rigoni , Valentín; Nouri , Alireza; Ali , Ramy; Keane , Andrew; O’Donnell , Terence (Frontiers in Electronics, 2021)
The Hybrid Power Electronic Transformer (HPET) has been proposed as an efficient and economical solution to some of the problems caused by Distributed Energy Resources and new types of loads in existing AC distribution systems. Despite this, the HPET has some limitations on the control it can exert due to its fractionally-rated Power Electronic Converter. Various HPET topologies with different capabilities have been proposed, being necessary to investigate the system benefits that they might provide in possible future scenarios. Adequate HPET models are needed in order to conduct such system-level studies, which are still not covered in the current literature. Consequently, this article presents a methodology to develop power flow models of HPET that facilitate the quantification of controllability requirements for voltage, active power and reactive power. A particular HPET topology composed of a three-phase three-winding Low-Frequency Transformer coupled with a Back-to-Back converter is modeled as an example. The losses in the Back-to-Back converter are represented through efficiency curves that are assigned individually to the two modules. The model performance is illustrated through various power flow simulations that independently quantify voltage regulation and reactive power compensation capabilities for different power ratings of the Power Electronic Converter. In addition, a set of daily simulations were conducted with the HPET supplying a real distribution network modeled in OpenDSS. The results show the HPET losses to be around 1.3 times higher than the conventional transformer losses over the course of the day. The proposed methodology offers enough flexibility to investigate different HPET features, such as power ratings of the Power Electronic Converter, losses, and various strategies for the controlled variables. The contribution of this work is to provide a useful tool that can not only assess and quantify some of the system-level benefits that the HPET can provide, but also allow a network-tailored design of HPETs. The presented model along with the simulation platform were made publicly available.